Visions of the Future of Craft Education - Mommo, Sanna; Kouhia, Anna; Rönkkö, Marja-Leena (Wiley-Blackwell, 2025)
This study examines the history of craft education, especially in the context of social and temporal changes, and envisions its future based on narratives collected by student teachers at two Finnish universities. The research material covers essay responses that discussed the future of craft education in the light of forecasted megatrends. The essay responses were analysed using narrative methods, and the results are presented as visions of the priorities and content of future craft education. While craft teaching today emphasises technology, well-being and communal living, the growth of digitality, sustainable education and materiality is likely to continue in the future. We envision that future craft education will focus on pedagogical content rooted in craft traditions, with a strong emphasis on skills education.